A large animal model of Spinal Muscular Atrophy and correction of phenotype - Duque, Sandra I. (Ann Neurol, 2015)
OBJECTIVES: Spinal muscular atrophy (SMA) is caused by reduced levels of SMN which results in motoneuron loss. Therapeutic strategies to increase SMN levels including drug compounds, antisense oligonucleotides or scAAV9 gene therapy have proved effective in mice. We wished to determine whether reduction of SMN in postnatal motoneurons resulted in SMA in a large animal model, whether SMA could be corrected after development of muscle weakness and the response of clinically relevant biomarkers. METHODS: Using intrathecal delivery of scAAV9 expressing a shRNA targeting pig SMN1, SMN was knocked down in motoneurons postnatally to SMA levels. This resulted in an SMA phenotype representing the first large animal model of SMA. Restoration of SMN was performed at different time points with scAAV9 expressing human SMN (scAAV9-SMN) and electrophysiology measures and pathology were performed. RESULTS: Knockdown of SMN in postnatal motoneurons results in overt proximal weakness, fibrillations on electromyography (EMG) indicating active denervation, and reduced compound muscle action potential (CMAP) and motor unit number estimates (MUNE), like human SMA. Neuropathology showed loss of motoneurons and motor axons. Pre-symptomatic delivery of scAAV9-SMN prevented SMA symptoms indicating all changes are SMN dependent. Delivery of scAAV9-SMN after symptom onset had a marked impact on phenotype, electrophysiological measures and pathology. INTERPRETATION: High SMN levels are critical in postnatal motoneurons and reduction of SMN results in a SMA phenotype which is SMN dependent. Importantly, clinically relevant biomarkers including CMAP and MUNE are responsive to SMN restoration and abrogation of phenotype can be achieved even after symptom onset.